Tiktok as a Media To Increase Students’ Interest in Learning English: A Study at School in Mandailing Natal at Xi Grade Senior High School - Widiya, Siska; Salmiah, Maryati (Institut Agama Islam Negeri Palopo, 2024)
Improving interest in learning is essential; without it, students may not absorb lessons well from the teacher. Using TikTok for learning English can enhance students' interest in learning the language. This research aimed to know students’ interest in learning English by using TikTok in the XI grade in SMA Negeri 1 Natal in the academic year 2023/2024. Meanwhile, TikTok videos can be utilized to increase students’ vocabulary, students’ motivation, and enthusiasm for English learning. The participants of this research were 36 students at XI grade SMA Negeri 1 Natal as a sample. This research was used as a qualitative descriptive method. In collecting the data, it employed questionnaires, interviews, and documentation as instruments. The questionnaire consists of 10 item questions and 5 questions in the interview. The result of this study is that students’ interest in using TikTok videos to increase students’ interest is highly effective. The questionnaire result, consisting of 10 items of questions, shows that the average interest score of students is 86% in the “Strongly Agree” category. In conclusion from the data is that the use of TikTok is very effective for students, so it can increase students' interest in learning English. Based on these findings, TikTok videos can be considered a productive and effective medium beneficial for increasing students’ interest.